2018
DOI: 10.1108/jhom-10-2017-0262
|View full text |Cite
|
Sign up to set email alerts
|

Doctor-patient communication: a review and a rationale for using an assessment framework

Abstract: Purpose The purpose of this paper is to explore the extent to which improving doctor–patient communication (DPC) can address and alleviate many healthcare delivery inefficiencies. Design/methodology/approach The authors survey causes and costs of miscommunication including perceptual gaps between how physicians believe they perform their communicative duties vs how patients feel and highlight thresholds such as the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) used by hospitals to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 64 publications
3
43
0
1
Order By: Relevance
“…This variable is especially important to consider as an influential factor for healing time and its potential association with patient satisfaction from chest masculinization surgery. Another explanation for this finding may be the possibility of increased doctor-patient communication, which has been linked with improved patient-reported outcomes (39). The process of learning from the patient, eliciting their concerns, and implementing and refining the surgical technique may have resulted in increased communication between the senior author and patients during that time period (39).…”
Section: Discussionmentioning
confidence: 99%
“…This variable is especially important to consider as an influential factor for healing time and its potential association with patient satisfaction from chest masculinization surgery. Another explanation for this finding may be the possibility of increased doctor-patient communication, which has been linked with improved patient-reported outcomes (39). The process of learning from the patient, eliciting their concerns, and implementing and refining the surgical technique may have resulted in increased communication between the senior author and patients during that time period (39).…”
Section: Discussionmentioning
confidence: 99%
“…study method: The data collection for the study was done using: (i) a predesigned self-administered questionnaire which included two parts: Likert scale from strongly agree to strongly disagree. Strongly agree and agree were considered 'high perception" for positive statements [1,3,6,7,8,9,10], while disagree and strongly disagree represented high perception for negative statements [2,4,5]. A total perception score was calculated; high perception was considered when the total score was greater than the mean.…”
Section: Aim Of Workmentioning
confidence: 99%
“…Surprisingly, most of the participants who were classified as having poor communication reported that they have enough information regarding doctorpatient communication (Table 1). This may be attributed to that physicians may frequently overestimate their ability to communicate in interpersonal interactions (Belasen and Belasen, 2018).…”
Section: Aim Of Workmentioning
confidence: 99%
“…Doctor-patient communication is one of the most essential dynamics in health care, affecting the course of patient care and patient satisfaction [1][2][3][4][5]. Although technical skills may receive more attention in physician training, communication plays an essential role in practice.…”
Section: Introductionmentioning
confidence: 99%